Palm Kernel Separation Efficiency and Kernel Quality from Different Methods Used in Some Communities in Rivers State, Nigeria - O.M, Akusu; D.B, Kiin-Kabari; L.I, Barber (Journal of Food Technology Research, 2017)
The separation efficiency and palm kernel quality of five palm kernel shell separation methods used in selected communities in Rivers State, Nigeria were evaluated. The methods include traditional handpicking, clay-water bath (kaolin), mechanical dry separation, pneumatic and hydrocyclone separations. The weight of recovered palm kernels obtained from each separation method was determined and used in the calculation of separation efficiencies. Free fatty acid (FFA), shell/fibre and moisture content of the palm kernels recovered from each separation method was determined. The results show that the least free fatty acid (FFA) content of (3%) was found in sample separated by the pneumatic method and highest (8%) in the clay-water bath (kaolin) method. High moisture content of 11% was recorded for kernels separated by clay-water bath (kaolin). Pneumatic separation method retained the least percentage of shell/fibre content (2%). Hand picking and clay-water bath (kaolin) methods had shell/fibre retention of 8% and 6%, respectively. However, mechanical, pneumatic and hydrocyclone separation techniques conform to the quality parameters when compared to SON/NIS standard. The mechanical, pneumatic and hydrocyclone separation methods gave higher separation efficiencies of 74, 90 and 96% respectively and palm kernels of superior quality that meets the palm kernel industrial standards. There was no significant difference (P>0.05) in separation efficiencies between the traditional hand picking and the clay water bath methods however there was a significant difference (P<0.05) between the above two methods and mechanical, pneumatic and hydrocyclone separation methods.